Becoming ethical through relational interaction: An examination of a performance among internally displaced persons in Nigeria. (1st September 2018) - Afolabi, Taiwo
Ethics is a set of moral principles that seeks to guide researchers from harming those they research. These moral principles aim to protect humanity, establish and sustain a progressive value system that respects and promotes human dignity. Although how ethical consideration is envisioned can be universal, how it is enacted and performed can be relative. It is based on certain contingences that are culturally specific and peculiar. In this article, I argue that irrespective of the universality of some ethical considerations, relational interaction becomes a guiding principle that makes how ethical protocols are achieved relative. Relational interaction emphasizes the other over oneself; hence, it is not transactional. It has at its core quality interaction because it does not maximize self-interest to the detriment of the other. Thus, as varied as these ethical issues are, I argue that what stands at the heart of any appropriate ethical protocol is qualitative humanistic interaction established on values of human dignity, respect, quality welfare, empathy and justice. The idea of relational interaction fosters collaboration, understanding, communication and relationship. These universal ethical protocols are advanced in specific ways as cultures interact and people interpret value systems. I investigate how ethical nuances were explored through performances in internally displaced people camps in Nigeria. Ethical protocol is another performance that positions artists to be responsible and be held responsible for moral practices. I conclude that relational interaction poses a dialogic, responsible, accountable and construction of self in relations to alterity and cultural ethos.